2023
DOI: 10.1186/s12875-022-01949-8
|View full text |Cite
|
Sign up to set email alerts
|

An innovative model of psychological service delivery in primary healthcare: the Single-Session Intervention

Abstract: Background In Canada, the demand for mental health care exceeds the provision of services. This exploratory study aimed to assess the feasibility and impact of a new service delivery model for psychological consultations in primary care settings: the Single-Session Intervention (SSI), inspired by Advanced Access (AA) principles for appointment scheduling. The specific objectives were to examine whether the SSI increases accessibility to psychological consultations, to measure the effects of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…However, they used a Wizard-of-Oz approach (i.e., a therapist pretending to be a chatbot) rather than a chatbot powered by GenAI. The single-session paradigm is designed to provide an immediate relief from the issue within one session and has become increasingly popular as a form of intervention given the high demand placed on counselling services to provide timely interventions (Hymmen et al, 2013); previous research has shown that in 51% of the cases, a single session was enough to resolve an issue (Perreault et al, 2023).…”
mentioning
confidence: 99%
“…However, they used a Wizard-of-Oz approach (i.e., a therapist pretending to be a chatbot) rather than a chatbot powered by GenAI. The single-session paradigm is designed to provide an immediate relief from the issue within one session and has become increasingly popular as a form of intervention given the high demand placed on counselling services to provide timely interventions (Hymmen et al, 2013); previous research has shown that in 51% of the cases, a single session was enough to resolve an issue (Perreault et al, 2023).…”
mentioning
confidence: 99%
“…The mother acquired more leisure time outside the family, the relationship between the mother and the younger daughter became appropriately distant, and the sibling bond between the patient and her sister deepened, contributing to the patient's acquisition of more emotional closeness, potentially replacing the mother-daughter relationship. In recent years, some studies have indicated that single-session therapy effectively treated mental disorders such as anxiety, depression, and eating disorders and physical diseases (19)(20)(21)(22). This approach is particularly beneficial for patients who may not be able to receive comprehensive psychotherapy due to limitations in their circumstances (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some studies have indicated that single-session therapy effectively treated mental disorders such as anxiety, depression, and eating disorders and physical diseases (19)(20)(21)(22). This approach is particularly beneficial for patients who may not be able to receive comprehensive psychotherapy due to limitations in their circumstances (19,20). We propose that single therapy or ultra-short-term psychotherapy could significantly contribute to the liaison-consultation process especially in general hospitals, as demonstrated by this case study.…”
Section: Discussionmentioning
confidence: 99%